Democratisation without Coercion: Parliamentary Bodies as Democracy Promoters in the Mediterranean. Issue 4 (4th July 2019) - Harwood, Mark A
Abstract: In an attempt to decentre the debate of democracy promotion in the Mediterranean, this article applies social constructivism to an analysis of the work undertaken by two International Parliamentary Bodies in the Mediterranean. With a focus on the European Parliament and the Parliamentary Assembly of the Mediterranean, we analyse how effective their role can be without coercion and move on to discuss whether newly formed democratic parliaments, as in Tunisia, may represent a more legitimate and viable source of parliamentary-driven democracy promotion.